Selection of optimal endarterectomy technique in the left anterior descending artery for diffuse coronary atherosclerosis - S. A. Belash; K. O. Barbukhatti; S. S. Shevchenko; E. P. Yasakova; A. S. Nekrasov; V. A. Porkhanov (Российский кардиологический журнал)
Aim. To determine the optimal method for performing coronary artery endarterectomy (СE) based on immediate and long-term outcomes of coronary artery bypass grafting (CABG) in combination with open or closed CE in the left anterior descending artery (LAD).Material and methods. This retrospective study included 103 patients who underwent CABG in combination with closed CE and 204 after open CE in the LAD during the period from 2003 to 2016. In both groups, the patient age was comparable (65 years [56; 69] vs 67 years [58; 72] (p=0,263)). There were more men (88,3% vs 81,4% (p=0,421). The mean follow-up period was 94 months [38; 180]. Long-term outcomes were assessed in 86,4% (n=89) and 83,8% (n=171) of patients from the closed and open CE groups, respectively (p=0,141). Angiographic data were studied in 75,3% and 67,3% of patients, respectively (p=0,441).Results. In the closed and open CE groups, in-hospital mortality was 4,8% and 1,5% (p=0,0012), incidence of perioperative myocardial infarction — 11,6% vs 2,5%, (p<0,001), survival rate after 7,8 years — 81,3±5,1% and 84,4±3,2% (p=0,342), respectively. The patency of arterial shunts was significantly higher in the open CE group — 93,1% vs 80,6% (p=0,004). At the same time, the patency of venous shunts in the long-term period between the groups was comparable — 70,1% vs 73,7% (p=0,314).Conclusion. Open CE in combination with CABG provides better immediate outcomes compared to closed CE. Long-term survival and freedom from angina between the groups were comparable. In the long-term period, the patency of internal thoracic artery after open CE is better than after the closed technique. Open CE is a safe and effective method to achieve complete myocardial revascularization in patients with severe diffuse LAD atherosclerosis.